2006
DOI: 10.1128/jb.188.4.1473-1488.2006
|View full text |Cite
|
Sign up to set email alerts
|

The Genome Sequence of the Obligately Chemolithoautotrophic, Facultatively Anaerobic Bacterium Thiobacillus denitrificans

Abstract: The complete genome sequence of Thiobacillus denitrificans ATCC 25259 is the first to become available for an obligately chemolithoautotrophic, sulfur-compound-oxidizing, ␤-proteobacterium. Analysis of the 2,909,809-bp genome will facilitate our molecular and biochemical understanding of the unusual metabolic repertoire of this bacterium, including its ability to couple denitrification to sulfur-compound oxidation, to catalyze anaerobic, nitrate-dependent oxidation of Fe(II) and U(IV), and to oxidize mineral e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
255
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 318 publications
(264 citation statements)
references
References 92 publications
7
255
0
2
Order By: Relevance
“…Hydrolytic fermentative acidogenic activity in anaerobic bioreactors is likely controlled by strict anaerobic bacteria like Longilinea, Clostridium, and Proteiniphilum (Yamada et al 2007;Kohda et al 1997;Letowski et al 2001;Chen and Dong 2005;Larsen et al 2009) and facultative aerobic bacteria such as Corynebacterium (Kampfer et al 2009). In the aerobic sludge, the high abundances of Thiobacillus, Comamonas, Diaphorobacter, Ottowia, and Weeksella (Table S8), which reportedly degrade several phenol and SCN − compounds (Felföldi et al 2010;Beller et al 2006;Klankeo et al 2009;Yuste et al 2000), were in accordance with the significant removal of pollutants in the final effluent. As referred in Table S8, the significant presence of PAHdegrading bacteria like Comamonas (Goyal and Zylstra 1996) and Diaphorobacter (Klankeo et al 2009) indicated the removal of corresponding pollutants in aerobic sludge leading to detoxification of CWW (Zhang et al 2013).…”
Section: Discussionmentioning
confidence: 68%
“…Hydrolytic fermentative acidogenic activity in anaerobic bioreactors is likely controlled by strict anaerobic bacteria like Longilinea, Clostridium, and Proteiniphilum (Yamada et al 2007;Kohda et al 1997;Letowski et al 2001;Chen and Dong 2005;Larsen et al 2009) and facultative aerobic bacteria such as Corynebacterium (Kampfer et al 2009). In the aerobic sludge, the high abundances of Thiobacillus, Comamonas, Diaphorobacter, Ottowia, and Weeksella (Table S8), which reportedly degrade several phenol and SCN − compounds (Felföldi et al 2010;Beller et al 2006;Klankeo et al 2009;Yuste et al 2000), were in accordance with the significant removal of pollutants in the final effluent. As referred in Table S8, the significant presence of PAHdegrading bacteria like Comamonas (Goyal and Zylstra 1996) and Diaphorobacter (Klankeo et al 2009) indicated the removal of corresponding pollutants in aerobic sludge leading to detoxification of CWW (Zhang et al 2013).…”
Section: Discussionmentioning
confidence: 68%
“…In addition to the group 3b hydrogenases previously reported from OD1 and OP11 genomes , we recovered group 3b sequences from two gammaproteobacterial genomes (ACD46 and ACD21) and a partial sequence from the ACD79 genomic bin of unknown taxonomic assignment (Supplementary Figure S8). Unlike the Archaeal sulf-hydrogenase homologs in the obligately fermentative Thermococcales, the physiological role for NADP group 3b hydrogenases in the Proteobacteria (for example, A. vinelandii and T. denitrificans) is not yet known (Beller et al, 2006). The ACD79 genome bin has a second hydrogenase, and along with sequences from the Chloroflexi (ACD34) and Deltaproteobacteria (ACD 62) genomes, is most closely related to group 3c sequences (Supplementary Figure S8).…”
Section: Metabolic Interdependencies In An Aquifer Microbial Communitmentioning
confidence: 99%
“…1A). The anodic current [at +0.4 V vs. standard hydrogen electrode (SHE)] was initially stable at ∼7 μA cm −2 , although it increased afterward, probably owing to the formation of conductive biofilms (23 contrast, T. denitrificans is a chemolithoautotrophic bacterium and known to use solid iron minerals (e.g., pyrite) as electron donors (22). We confirmed that the metal-oxide electrode (at −0.4 V vs. SHE) served as an electron donor for T. denitrificans in the presence of nitrate (Fig.…”
Section: Electrochemical Characteristics Of Catabolic Reactions In Momentioning
confidence: 99%
“…IET mechanisms described so far are based on diffusion of redox chemical species (20) and/or direct contact in cell aggregates (21). To address the involvement of conductive minerals in IET, we constructed mixed cultures of two representative soil bacteria, G. sulfurreducens (2,5) and Thiobacillus denitrificans (22), in the presence and absence of iron-oxide minerals, and their IET-dependent cooperative catabolic reactions were investigated.…”
mentioning
confidence: 99%